Analisis Faktor-Faktor yang Mempengaruhi Kreativitas Kerja pada Komisi Pemilihan Umum Kota Padang - Yentisna, Yentisna; Maivalinda, Maivalinda; Efendi, Syahrul (Jurnal Kajian Manajemen Bisnis, 2014)
Employee creativity is influenced by various factors. This study analyzes the factors that affect the creativity of the employees of the General Election Commission (KPU) in Padang. The factors that made the object of study in this research include: salary, job suitability of personality and co-workers. Data were obtained from questionnaires and direct observation in the field. Data were analyzed using multiple linear regression . Based on the research it can be concluded that the above factors are dominant to influence employee creativity, but not everything is absolutely applicable to all employees as they relate to each individual. Based on the F-test value is close to zero, it is seen that the suitability of personality variables simultaneously, co-workers and salary have an influence on employee creativity. Suggestions put forward the results of this research is to increase the ability of colleagues to work together, work together to solve problems. While the boss is expected to hear directly and understand the complaints and opinions about problem-solving work, cooperation partners and implementation of national elections